The Effect of Patient Waiting Time on Outpatient Satisfaction at Siti Aisyah Islamic Hospital Madiun - Ummi Durrotun Nasyicha; Karina Nur; Retno Widiarini (Health Science UDINUS, 2023)
Patient satisfaction is patient expectation which arises from the actions of health workers as a result of the performance of health services during the process of interacting in an effort to provide services. Patient satisfaction with patient registration services is influenced by waiting times. The waiting time is the time used by patients to get services from registering until arriving at the doctor's examination room. Based on the results of a preliminary study at Islamic Siti Aisyah Hospital Madiun, it is known that out of 10 that have been observed, that 7 (70%) respondents in the outpatient unit of RSI Siti Aisyah Madiun rated less satisfied with the waiting time (>60 minutes) not according to the standard while 3 (30%) respondents considered very satisfied with the waiting time (≤ 60 minutes) according to the standard. This study aims to determine the effect of patient waiting time on outpatient satisfaction. This type of research is quantitative cross sectional. The population is 2400 respondents. A sample of 96 respondents. Sampling technique using quota sampling, Data collection method using questionnaire. The data analysis used in this study was bivariate using the chi square test. The results of this study showed a Sig value of 0.046<0.05. The conclusion of this study is the effect of waiting time on patient satisfaction